Configurational pathways to post-COVID-19 economic recovery in the high-end hotel sector of Shandong Province, China: evidence from csQCA - Wang, Yunhan; Zhu, Xuanyu; Wang, Shuai (Frontiers in Sustainable Tourism, 2025)
IntroductionThe COVID-19 pandemic severely impacted the global hotel industry. In early 2020, the occupancy rate of high-end hotels in China dropped by more than 50%. In Shandong Province, the revenue loss exceeded 60%, which raised urgent questions about post-pandemic recovery. This study explores how the combination of operations and financial conditions affects the survival or decline of hotels. Drawing on Lipset's theory of institutional collapse and economic recession.MethodologyWe conducted a study of 20 high-end hotels in Shandong Province using the clear set qualitative comparative analysis (csQCA) method. Four variables—average room rate index (ARI), contribution to operating profit (CTP), total operating profit margin (GOP), and revenue generation index (RGI)—were transformed into binary sets to determine causal relationship patterns.ResultsThe research results reveal three empirical models for economic survival and five models for decline. No single factor is indispensable. Resilient hotels typically combine high operating profit margins with favorable pricing or revenue generation, while unbalanced financial structures increase the risk of decline.DiscussionThis study contributes to the research on crisis recovery. It depicts the path of resilience and demonstrates the value of the conditional qualitative analysis (csQCA) method in capturing the complex and interrelated operating conditions of hotels in extreme disruptions.